Knowledge and Attitude Towards Sexual Practices During Pregnancy - Fatima, Sadia; Shafiq, Nighat; Muzaffar, Tabassum; Abbas, Syed Waqar; Zohra, Sadaf; Safdar, Isma (Pakistan Armed Forces Medical Journal, 2022)
Objective: To explore the knowledge, attitude and sexual practices among pregnant women reporting to a tertiary care hospitalStudy Design: Cross-sectional analytical study.Place and Duration of Study: Antenatal clinic of Obstetrics & Gynaecology Department, Combined Military Hospital Rawalpindi Pakistan, from Jan to Jun 2020.Methodology: Three hundred and seventy women who attended the antenatal clinic during the study period were interviewed. The responses to chosen preferences were recorded on a structured questionnaire.Results: The majority of participants believed that intercourse could be done throughout pregnancy, it does not result in complications, and improves marital relationships. However, it was difficult due to the changed physical appearance, but it was not unpleasant for the husband. Only 51.1% of participants agreed to decreased libido. 77.6%, 71.6% and 75.4% were of the opinion that it was not prohibited in religion, neither influence baby nor labour respectively.Conclusion: Most pregnant women maintain sexual activity during pregnancy. The majority had adequate knowledge and a positive attitude.